ANALISIS KEMAMPUAN BERPIKIR KRITIS MAHASISWA PENDIDIKAN FISIKA SEMESTER 3 TENTANG PEMANFAATAN TEKNOLOGI SOLAR CELL TERHADAP LINGKUNGAN - Rosdiana Afifah Rahman; Sudarti Sudarti (Universitas Tanjungpura, Prodi Pendidikan Fisika, 2021)
This article aims to analyze students' understanding of the purpose of solar cell technology. Because the role of students is very important in developing one of the renewable energies that is solar cells. There are still many people who have not seen other benefits from the sun, as well as ways to use solar energy for other processes, such as the use of solar cells in households and so on. Most of humans have not seen other ways and benefits of solar energy. So that to socialize the use of solar cell technology, students need to understand how important solar energy is as a renewable energy and how to use it. The method used in this study used quantitative descriptive, with the sample of 2019 class of physics education students.